State - Region - Field - Enterprise: Framework of Economics System Stability of Russia. Part 1 - Kleyner, Georgy Borisovich (Economy of Regions, 2015)
In the article, the factors of a stability of the Russian economy are investigated from the systematic positions as a multilevel, multisubject and multidimensional socio-economic system. The concept of economics system stability as abilities to keep prerequisites for growth with the support and effective use of system structure of economy is formulated. The leading role of all economic subjects of different levels (including government as a subject of the international relations, regions as subjects of Federation, enterprises as economic entities) in economic stability is shown. The need of «extension» of a network of subjects due to strengthening of the subjectivity of economic fields is emphasized. Research of an internal basic system structure of an economic subject and external structure of its immediate environment in socio-economic, administrative-and-managerial, and market spaces with the use of the results of the new theory of economic systems leads to a conclusion of similarity of these structures. It is shown that each of these system complexes includes (together with a subject) four systems of various types - object, environmental, processed, and designed. The system environment of a subject in the administrative-and-managerial space of inter-level interactions has the same structure. It gives the chance to reduce a problem of subjects' resistance to a question of balance of system structures of the complexes forming an internal filling and an external environment of subjects. The method of balance index of similar complexes is given. Recommendations on a choice of the measures of economic policy for providing economics system stability of Russia during the crisis are formulated. It is shown that such policy has to be developed with the principles of a subject-preservation, system balance of internal filling and external environment of subjects, a corporate solidarity of subjects despite their level in the administrative hierarchy.